Preferencje rolników w zakresie planowania - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
In the paper, the farmers' needs in scope of planning are presented. For farmers, the most important information is that determining what and how is to be produced. Moreover, they demand financial information about their businesses. The character and regularity of information required by farmers depended on their individual decisions with regard to activity objectives (such as survival on the market or financial situation improvement for instance). The farmers pointed out the necessity of building plans of farm activity for various length of the time, i.e. short-term, middle term and long-term plans.